2022
DOI: 10.1029/2021jd036411
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Secondary Ice Production in Southern Ocean Maritime Boundary Layer Clouds

Abstract: Maritime boundary layer clouds in the SO have a significant shortwave (SW) cloud radiative effect associated with them (Haynes et al., 2011), and consequently they have an important role when estimating climate sensitivity to cloud feedbacks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 183 publications
1
22
0
Order By: Relevance
“…Further, the PID scheme suggests ice growth occurs with decreasing altitude in convective clouds, with P[large ice] ∼10% 150 m below cloud top and P[large ice] ∼50% 700 m below cloud top. This is consistent with previous studies that have shown higher updraft velocities provide a preferential environment for the growth of ice in supersaturated regimes (McFarquhar et al, 2011;Rosenow et al, 2014;Wang et al, 2020), and that SIP during SOCRATES was enhanced in convective regions exhibiting multiple updrafts (including embedded convective elements within stratocumulus clouds), with thin stratiform clouds with a lack of significant updraft activity exhibiting little SIP and remaining mostly composed of SLW (Järvinen et al, 2022;Lasher-Trapp et al, 2021;Mace et al, 2021). The peak P[any ice] for any part of the cloud averaged among both methods is ∼65% for convective clouds and ∼20% for stratiform clouds, suggesting that ice is about 3 times more likely in convective clouds than in stratiform clouds.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Further, the PID scheme suggests ice growth occurs with decreasing altitude in convective clouds, with P[large ice] ∼10% 150 m below cloud top and P[large ice] ∼50% 700 m below cloud top. This is consistent with previous studies that have shown higher updraft velocities provide a preferential environment for the growth of ice in supersaturated regimes (McFarquhar et al, 2011;Rosenow et al, 2014;Wang et al, 2020), and that SIP during SOCRATES was enhanced in convective regions exhibiting multiple updrafts (including embedded convective elements within stratocumulus clouds), with thin stratiform clouds with a lack of significant updraft activity exhibiting little SIP and remaining mostly composed of SLW (Järvinen et al, 2022;Lasher-Trapp et al, 2021;Mace et al, 2021). The peak P[any ice] for any part of the cloud averaged among both methods is ∼65% for convective clouds and ∼20% for stratiform clouds, suggesting that ice is about 3 times more likely in convective clouds than in stratiform clouds.…”
Section: Discussionsupporting
confidence: 93%
“…This section discusses methods of identifying cloud phase using both the in situ and remote-sensing data, and compares the identified phases for collocated remote sensing and in situ observations. Detailed information about the in situ and remote probes installed on the NCAR/NSF GV during SOCRATES, their operating characteristics, and the algorithms used to process the data are discussed elsewhere (e.g., D'Alessandro et al, 2021;Järvinen et al, 2022;McFarquhar et al, 2021;Wang et al, 2020;Zaremba et al, 2020Zaremba et al, , 2021. Thus, only a brief summary is provided here together with a focus on unique aspects of the processing required for this analysis.…”
Section: In Situ Datamentioning
confidence: 99%
“…Järvinen et al. (2022) found that the measured Ni concentrations are 1–2 orders of magnitude higher than the measured INP concentrations when the temperature is smaller than −10°C, and are up to 5 orders of magnitude higher when the temperature is larger than −10°C during SOCRATES. Their results also suggested the importance of other SIP in addition to the HM process on the ice production in SO clouds.…”
Section: Introductionmentioning
confidence: 90%
“…A more prominent mechanism is referred to as the Hallett-Mossop process, which is characterized by splintering of small ice particles off of graupel during riming (Hallett & Mossop, 1974). Previous studies have noted its likely presence over the Southern Ocean (Huang et al, 2021;Järvinen et al, 2022), although this process is primarily restricted to temperatures from −8° to −3°C where the greatest liquid phase frequency differences are not observed.…”
Section: Ccn Related To Cloud Phasementioning
confidence: 99%